2010
DOI: 10.3390/molecules15064227
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Carbohydrates in Natural and Cultured Cordyceps by Pressurized Liquid Extraction and Gas Chromatography Coupled with Mass Spectrometry

Abstract: Free and polymeric carbohydrates in Cordyceps, a valued edible mushroom and well-known traditional Chinese medicine, were determined using stepwise pressurized liquid extraction (PLE) extraction and GC-MS. Based on the optimized PLE conditions, acid hydrolysis and derivatization, ten monosaccharides, namely rhamnose, ribose, arabinose, xylose, mannose, glucose, galactose, mannitol, fructose and sorbose in 13 samples of natural and cultured Cordyceps were qualitatively and quantitatively analyzed and compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 31 publications
(33 reference statements)
0
36
0
Order By: Relevance
“…PLE can generally operate under high pressure and temperature to efficiently extract carbohydrates from different matrix, providing faster extractions, lower solvent consumption, and higher extraction efficiency [14][15][16][17]. Ultrasonic assisted-dispersive liquid-liquid microextraction (UA-DLLME) is another new extraction and enrichment technique for using very low volumes of organic solvent [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…PLE can generally operate under high pressure and temperature to efficiently extract carbohydrates from different matrix, providing faster extractions, lower solvent consumption, and higher extraction efficiency [14][15][16][17]. Ultrasonic assisted-dispersive liquid-liquid microextraction (UA-DLLME) is another new extraction and enrichment technique for using very low volumes of organic solvent [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…There is possibility of its role in synergetic effect with other compounds for several therapeutic effects. Further, the presence of Dmannitol (Guan et al 2010) and butylated hydroxytouline (Yu et al 2012) in considerable amount in O. sinensis can be another possible reason for its acclaimed healing properties as well as vigor and vitality. The effectiveness of O. sinensis as infusion with other herbs also deserves attention.…”
Section: Discussionmentioning
confidence: 99%
“…Guan et al (2010) reported occurrence of more than 7.99% free mannitol in natural but less than 5.83% mannitol in cultured O. sinensis. Zhu et al (1998a) classified seven classes of chemical constituents in natural and mycelium fermentation of O. sinensis as sterols, nucleosides, sugar derivatives, fatty acids, organic acids, proteins and vitamins.…”
Section: Pharmacologically Active Metabolitesmentioning
confidence: 94%
“…Chinese Pharmacopoeia (2010 Edition) documented that the ratio of mannose and glucose in Dendrobii Officinalis Caulis should be 2.4-8.0 (114). The monosaccharide profiles released from polysaccharides have also been used to discriminate different sweet medicines and identify their origins (115)(116)(117)(118). The results of those studies indicate that free sugars or sugar profiles obtained after acidic or enzymatic hydrolysis (i.e., amounts and composition of monosaccharides) are crucial for QC of polysaccharides.…”
Section: Quantification Analysismentioning
confidence: 93%